A Multi-Objective Dispatching Optimisation for Regional Bus Energy Saving - ZHANG, Yaqiong; WEI, Yuguang; YANG, Xinfeng; WU, Xu (Promet - Traffic&Transportation, 2025)
As energy conservation and sustainability become key priorities in public transportation, optimising bus scheduling with an emphasis on energy efficiency offers a practical pathway toward greener transit systems. However, existing studies often treat energy consumption and service quality in isolation, lacking an integrated framework for regional bus dispatch optimisation. This study proposes a multi-objective energy-saving dispatch model that jointly minimises passenger waiting time and vehicle energy consumption while considering vehicle allocation and passenger transfers. A vehicle-specific power (VSP)-based energy estimation method is introduced to enhance the accuracy of energy consumption assessments under real-world operating conditions. To solve the proposed model, we develop a two-phase optimisation algorithm that balances computational efficiency and solution quality. A case study on the Lanzhou regional transit network validates the model’s feasibility, demonstrating improvements in both service levels and energy consumption. The findings contribute to the development of more sustainable and efficient regional bus scheduling strategies.